2023
DOI: 10.3389/fcimb.2023.1144254
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vaginal microbiome composition does not affect development of the infant gut microbiome in early life

Abstract: Birth mode has been implicated as a major factor influencing neonatal gut microbiome development, and it has been assumed that lack of exposure to the maternal vaginal microbiome is responsible for gut dysbiosis among caesarean-delivered infants. Consequently, practices to correct dysbiotic gut microbiomes, such as vaginal seeding, have arisen while the effect of the maternal vaginal microbiome on that of the infant gut remains unknown. We conducted a longitudinal, prospective cohort study of 621 Canadian preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Dos Santos and colleagues revealed in a longitudinal study of 621 pregnancies that the infant gut microbiome composition at 10 days and 3 months postpartum was not associated with the maternal vaginal microbiota during delivery. Further assessment of other factors that could alter the infant microbiome, including: intrapartum antibiotics, breastfeeding, infant sex, chorioamnionitis, and maternal ethnicity revealed that maternal antibiotic administration during labor and delivery significantly affected infant gut microbiome composition 80 . In a cross‐sectional study of 1019 pregnancies, Gardemeister et al.…”
Section: Factors That Influence the Early‐life Microbiota In Connecti...mentioning
confidence: 99%
“…Dos Santos and colleagues revealed in a longitudinal study of 621 pregnancies that the infant gut microbiome composition at 10 days and 3 months postpartum was not associated with the maternal vaginal microbiota during delivery. Further assessment of other factors that could alter the infant microbiome, including: intrapartum antibiotics, breastfeeding, infant sex, chorioamnionitis, and maternal ethnicity revealed that maternal antibiotic administration during labor and delivery significantly affected infant gut microbiome composition 80 . In a cross‐sectional study of 1019 pregnancies, Gardemeister et al.…”
Section: Factors That Influence the Early‐life Microbiota In Connecti...mentioning
confidence: 99%
“…Also, Dominguez-Bello et al (2010) demonstrated that neonates born vaginally have a microbiota resembling the vaginal microbiome, enriched with Lactobacillus and Prevotella species, although other bacteria, such as the Enterobacteriaceae family, including Escherichia or Klebsiella , are also present ( Selma-Royo et al, 2019 ). On the contrary, Dos Santos et al (2023) conducted a longitudinal, prospective cohort study of 621 Canadian mother-newborn pairs and collected pre-delivery maternal vaginal swabs and infant stool samples at 10-days and 3-months of life. The aim was to evaluated the effect of maternal vaginal microbiome composition on the development of the infant stool microbiome.…”
Section: Microbial Colonization and Their Evolution During The First ...mentioning
confidence: 99%
“…Very recently, two large studies have shown that on the one hand, vaginal seeding (swabbing caesarean-section babies with their mother's vaginal fluids to boost the development of their microbiome) is safe and possibly might improve newborns' brain development [10]. Rather unexpectedly, it was found that maternal vaginal microbiome composition at delivery does not significantly affect infant stool microbiome composition and development, suggesting that practices to influence infant stool microbiome composition should consider factors other than maternal vaginal microbes [11].…”
Section: De Velopment Of the G Ut Microb Iotamentioning
confidence: 99%
“…Indirect central effects might occur through activation of G protein-coupled receptors expressed in the CNS or through epigenetic modulation of histone deacetylases [21]. Studies conducted as early as the 1990s demonstrate that gut bacteria not only respond to host neurochemicals; they are also able to produce some of these themselves [11,18]. Lactobacillus spp., Escherichia spp., and Bifidobacterium spp.…”
Section: Metabolic Pathwaymentioning
confidence: 99%